The modulating effect of bruxism as a form of suppressed hostility on depression in a selected population of tension type headache (ttha) and craniomandibular disorders (cmds) individuals - Molina, Omar Franklin; Peixoto, Marcus Sobreira; Aquilino, Raphael Navarro; Rank, Rise (Cadernos UniFOA, 2017)
AIMS: explore the hypothesis that bruxism and depression are forms of suppressed hostility in individuals presenting Craniomandibular Disorders (CMDs) and Tension-type Headache (TTHa). METHODS: We evaluated a group of 100 Craniomandibular Disorders and Tension-Type Headache individuals, a group of 38 CMDs and Facial Pain individuals and a group of 23 No Craniomandibular Disorders No Facial Pain individuals. Clinical examination, questionnaires, history of signs and symptoms, the Beck Depression Inventory (BDI) and the Cook-Medley Inventory (HO) were used to gather data. RESULTS: The frequency of Tension Type Headache was about 43.5% in the group of 230 Craniomandibular Disorder patients. Mean scores in hostility were 19.0, 17.7 and 17.2 in the groups presenting Tension-Type Headache and CMDs, CMDs and Facial Pain and No CMDs no Pain, respectively. Mean scores in depression were about 12.0, 9.1 and 5.7 respectively in the same groups. Mean scores in bruxism were about 12.9, 8.2 and 6.8, respectively in the same groups. The strongest correlation between bruxism and depression were observed in the TTHa group (r=0.4, p<0.0001) and in the Non CMD Non Pain group (r=0.48, p<0.02). CONCLUSION: Depression is a better indicator of hostility in subgroups presenting TTHa. Scores in bruxism and depression as a form of suppressed hostility are higher in CMDs and TTHa individuals than in controls without TTHa. Because scores in bruxism were higher in TTHa and CMDs individuals, there is a strong and positive association between bruxism and TTHa in individuals with concomitant Craniomandibular disorders.